Innovation and entrepreneurship: Successful experiences in Brazil and Peru - Barcellos-Paula, Luciano; Alvares, Daniela Fantoni; De Castro Rezende, Aline (Proceedings of the European Conference on Innovation and Entrepreneurship, ECIE, 2018)
Entrepreneurship plays an important role in the development of economies. In Latin America, specifically, public and private incentives for innovation are fundamental to enhance competitiveness and to strengthen new businesses. In this context, the paper aims to show the scenario of innovation and entrepreneurship in Brazil and Peru from the perspective of development programs, as well as to highlight the policies aimed at improving the quality and impact of the enterprises. In this context, we analyse the government, private and non-profit sector initiatives that deal with programs, projects, and actions to stimulate entrepreneurship and innovation, along with public policies that have an impact on the creation of positive environments for business development, and innovation networks. The focus of the study will be on the policies that are developed throughout the national territory in the studied countries, especially the exchange of experiences in Latin America. Preliminary results point out the importance of public power in the process of encouraging and consolidating innovation and entrepreneurship in these territories. It should be noted that institutions with business activities are essential in the ecosystem of innovation and corporate structure, especially in the smaller ones. Therefore, research in this field is fundamental for guiding development policies and stimulating business competitiveness. In summary, this paper proposes a relevant research on innovation and entrepreneurship, which is very useful to the public and private sectors and to the academic field since it aims to encourage the development of more effective research on the subject.
Keywords: Entrepreneurship; Innovation policy; Brazil Peru; https://purl.org/pe-repo/ocde/ford#5.02.00